2018
DOI: 10.3329/bmrcb.v43i2.35185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-HBc total positivity in an impoverished Urban Community in Banglades

Abstract: The infection with the Hepatitis B virus (HBV) is a global health problem. Hepatitis B virus (HBV) infections are rapidly spreading in developing countries due to the lack of health education, poverty, illiteracy and Hepatitis B vaccination. No widespread population based data of HBV is available in the country. So, a population-based serological survey was done to determine the prevalence of the Hepatitis B core antibody total (IgM+IgG) in an impoverished Urban Community in Dhaka, Bangladesh. A descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…One study in the Kalyanpur slum at Dhaka showed that the prevalence of anti-HBc total was 47.6%. 11 In South East part of Bangladesh (Sylhet) there is no such data. This study estimated the total core antibody status in the unvaccinated general population in a community in north eastern part of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…One study in the Kalyanpur slum at Dhaka showed that the prevalence of anti-HBc total was 47.6%. 11 In South East part of Bangladesh (Sylhet) there is no such data. This study estimated the total core antibody status in the unvaccinated general population in a community in north eastern part of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…2 As part of South Asia, Bangladesh was reported to be one of the top 10 burdened countries for viral hepatitis due to the lack of health education, illiteracy, poverty, and a lack of HB vaccination. [10][11][12] Consequently, Bangladesh has an intermediate chronic HB prevalence estimated at 2%-6% although epidemiology may vary between geographic regions and sociodemographic factors. 10 As mentioned earlier, the prevalence of HB is increasing over the world, therefore, prevention is seen as one of the best ways to protect people's health.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the situation, the WHO Western Pacific Region has a massive burden of HB infection, while the WHO South‐East Asia Region has 18 million 2 . As part of South Asia, Bangladesh was reported to be one of the top 10 burdened countries for viral hepatitis due to the lack of health education, illiteracy, poverty, and a lack of HB vaccination 10–12 . Consequently, Bangladesh has an intermediate chronic HB prevalence estimated at 2%–6% although epidemiology may vary between geographic regions and sociodemographic factors 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In HBV endemic area prevalence of Anti HBc is high.In Bangladesh prevalence of AntiHBcamong general population is 31% 2 ,among chronic kidney disease patient is 39.3% . Another study conducted in Kallyanpur, a densely populated community in Dhaka, Bangladesh explored its prevalence is 47.7% among 384 healthy subjects 5 . General populations as well as physicians arevery much worried about Anti HBc positivity.…”
Section: Introductionmentioning
confidence: 99%